The Influence of Job Training, Physical Work Environment on Job Achievement Mediated by Work Motivation PT. Petronesia Benimel Head Office Jakarta - Angga Wirandono, Audya; Isa Indrawan, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research aims to analyze the influence of job training and the physical work environment on job performance mediated by work motivation at PT Petronesia Benimel Head Office Jakarta. This research uses associative quantitative research and uses primary data sources. This research was conducted at PT Petronesia Benimel Head Office Jakarta. The population in this study was 60 employees and used a saturated sampling technique to calculate the sample. Data were collected by distributing questionnaires, this research model uses analytical tools and the research measuring tool uses Smart PLS version 3. The results of this research are as follows: Job training has an insignificant negative effect on employee work performance. The work environment has a significant positive effect on employee work performance. Job training has an insignificant negative effect on employee work motivation. The work environment has a positive and significant effect on employee work motivation. Work motivation has a positive and significant effect on employee work performance. Job training has a positive and significant effect on work performance through work motivation of employees. The work environment has a positive and significant effect on work performance through employee work motivation at PT. Petronesia Benimel Head Office Jakarta.